Intensive Care Unit Nurses in Iran: Occupational Cognitive Failures and Job Content - Fatemeh Mehri; Amin Babaei-pouya; Mansoureh Karimollahi (Frontiers Media S.A., 2022)
BackgroundNurses in intensive care units (ICU) are under a lot of stress because of special conditions caused by the work environment and the high level of knowledge and skills required to work in these units, which can lead to cognitive failures. This study aimed to investigate the relationship between occupational cognitive failures (OCF) and job content (JC) in nurses in the ICU of Ardabil hospitals in 2020.MethodsThe present study was a descriptive-analytical cross-sectional study that was conducted in 2020. The study population included nurses working in the ICU of hospitals in Ardabil, from which 267 people who were eligible to enter the study were selected. OCF and JC questionnaires were used to collect data. Data were analyzed using SPSS software 23.ResultsOCF with work records in the ICU, total work records, and work records in the COVID-19 and non-COVID-19 units are significantly associated. OCF was inversely related to the JC subscales of skill discretion and decision authority. And directly related to other subscales of JC.ConclusionsDevelop job ability, reduce repetitive tasks, create diversity in work, create opportunities for creativity, have the authority and freedom to make decisions, facilitate work with new technologies, have enough time to do work, have a friendly work environment with colleagues, support by the supervisor, improving posture, especially for the upper body, feeling job security can help to reduce the cognitive failure of nurses.